2013
DOI: 10.1177/1363460712471117
|View full text |Cite
|
Sign up to set email alerts
|

Identity diversification among transgender sex workers in Thailand’s sex tourism industry

Abstract: This article looks at identity diversification among Thai (MTF) transgender sex workers who are in a semi-reassigned physical state; working in two famous sex tourism hot spots in Thailand. Locating the informants in their own gender system, then drawing on western queer and transgender theories, we examine the negotiation of gender and identity in this unique cultural, historical and political context. The research shows that the sex industry facilitates the emergence of new third-gender identities among MTF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…Here, the literature tends to focus on ideas around embodiment with the aim of expanding conceptualisations of gender through positing gender performativity as a legitimate freestanding gender marker (e.g. embodying a female aesthetic and identifying as such, modifying the body through gender reassignment surgery, and performing heterosexual sex) (Ocha 2013;Ocha and Earth 2013). Literature on sex work from other contexts has considered the experiences of MSM and transgender women (often, and incorrectly, together), however, this literature has primarily been concerned with how non-conforming gender identities influence sexual practices (see: Baral et al 2014 andDecker et al 2014).…”
Section: Sex Work Identity and Healthmentioning
confidence: 99%
“…Here, the literature tends to focus on ideas around embodiment with the aim of expanding conceptualisations of gender through positing gender performativity as a legitimate freestanding gender marker (e.g. embodying a female aesthetic and identifying as such, modifying the body through gender reassignment surgery, and performing heterosexual sex) (Ocha 2013;Ocha and Earth 2013). Literature on sex work from other contexts has considered the experiences of MSM and transgender women (often, and incorrectly, together), however, this literature has primarily been concerned with how non-conforming gender identities influence sexual practices (see: Baral et al 2014 andDecker et al 2014).…”
Section: Sex Work Identity and Healthmentioning
confidence: 99%
“…I gave up sexual pleasure and a piece of my soul to earn a living as a prostitute [in the tourism industry]' (Aldous et al 2008, 152). Moreover, depending on the availability of financial resources and their ability to gain access to affordable health care services, it is not uncommon for some kathoeys to be dissatisfied with the outcome of the surgical procedures that they have undergone (Ocha and Earth 2012). Further, due to an intensive re-sculpting of the body, even in semi-reassigned ones, many do not have a very long life expectancy.…”
Section: Qh Tanmentioning
confidence: 94%
“…In this regard, there is some potential for the stubborn dichotomies of masculinityfemininity and heterosexuality-homosexuality to be dismantled. Hence, some scholars have tacitly indicated that kathoey tourism affords a conducive space for the emergence of variegated gender and sexual subjectivities that may include more liminal, complex and alternative positionalities (O'Flaherty 1990;Manderson 1992Manderson , 1995Ocha and Earth 2012;Ocha 2014). It has even been implied that kathoeys could be forerunners in the pursuit of gender equality and erotic justice, a pursuit that is firmly transnational in nature.…”
Section: Qh Tanmentioning
confidence: 94%
See 2 more Smart Citations